Social Progress for Resilient Regions: Speech of the EIB Vice President Pim van Ballekom - ERSA Congress 2017 - van Ballekom, Pim (REGION, 2018)
This paper is the base text for the speech of the EIB Vice President Mr. Pim van Ballekom on the ERSA Congress in Groningen, on August 2017. This text which represents his and the Bank’s views on the topic “Social Progress for Resilient Regions”. Although in his speech he deviated from the prepared speech to react on topics raised by the other speakers, this text and its contents remain valid.